(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The system of accounting information role in the success of the economic unit, whether for-profit or non-purposeful, and through the availability of financial reports of information accounting for quality properties in the financial reports, which are the final product of all departments, sections and other parties, including help in strengthen the decisions of the administration and operations of Information economic Unity. The municipalities of economic units, non-profit, which is characterized by certain characteristics, including the multiplicity of activities (service, productivity, construction) and multiple sources of access to resources, so the accounting information system that seeks to provide decision makers with information on the investigation and use of resources, leading to improved services and activities .Therefore, it has gained importance of research by providing a framework for the application of accounting system for municipalities, provides quality features to help stakeholders in the decision-making and planning, control and evaluation of performance information.